Locality and belonging - Lovell, Nadia, 1963- (European Association of Social Anthropologists (Series), 1998)
Locality and Belonging provides an international overview of the relationship between identity and territory with case studies from Indonesia, Zanzibar, Argentina, South Africa and the UK.